ANALISIS KLASTER DENGAN METODE K-MEANS PADA PERSEBARAN KASUS COVID-19 BERDASARKAN DESA DI KECAMATAN KEMANG – BOGOR - Yuni Permata Sari; Basir, Choirul (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
Coronavirus (Covid-19) is a new type of virus found in humans in Wuhan Province, China at the end of 2019. Indonesia is one of the countries infected with the Covid-19 virus. The purpose of this study is to group the distribution of Covid-19 cases by village in Kemang-Bogor District by applying the K-Means method. The data used in this study is secondary data on the variables of the spread of Covid-19 from January to August 2021. The grouping was carried out based on the parameters of the number of confirmed positive cases, recovered, and died. In this study, to group the data, the K-Means method and the Euclidean distance measurement method were used. Based on the results of the study, it is shown that the K-Means Clustering method can be applied to group villages in Kemang-Bogor District with the optimal cluster located at k = 3 which means that the recommended cluster is 3 clusters with cluster 1 containing 6 villages, cluster 2 containing 1 village, and cluster 3 containing 2 villages.